ANALISIS PENGELOLAAN KOIN NU DALAM PEMBIAYAAN KEBUTUHAN DASAR RANTING OLEH UPZISNU (DESA JANTIGANGGONG) - Efendi, Saiful Nggufron; Rahman, Hidayatur; Kotimah, Siti (Bisnis-Net, 2024)
The purpose of this research is to manage NU coins for financing needs program, starting from condolence donations for Jantiganggong villagers who have lost family members, donating alms to orphans and dhuafa and financing routine religious activities. In addition, the results of this study were able to share understanding with the residents of Jantiganggong village and its surroundings regarding the management of NU coins in distributing village needs which was carried out transparently and in accordance with institutional procedures. The methodology used in this study uses a qualitative approach. This approach is used because research functions to create descriptive data such as words, writing, behavior from the research. The result of this study are the proper management of NU coins for village needs financing program managed by UPZISNU Jantiganggong village, which will provide benefits to local residents with the existence of a grief compensation program, compensation for orphans, compensation for widows and poor people as well as religious event. With this report it is hoped that Jantiganggong villagers who have participated in the NU coin movement will not worry that the infaq that has been collected will be distributed according to the target and carried out transparently according to predetermined procedures. With this movement, it is hoped that all the people involved will understand more about the importance of infaq, not the nominal infaq. Therefore, from the NU coin movement, the infaq that is collected is in the form of coins or coins, so that all levels of society can spend lightly